2014
DOI: 10.1289/ehp.1307294
|View full text |Cite
|
Sign up to set email alerts
|

White Light–Emitting Diodes (LEDs) at Domestic Lighting Levels and Retinal Injury in a Rat Model

Abstract: Background: Light-emitting diodes (LEDs) deliver higher levels of blue light to the retina than do conventional domestic light sources. Chronic exposure to high-intensity light (2,000–10,000 lux) has previously been found to result in light-induced retinal injury, but chronic exposure to relatively low-intensity (750 lux) light has not been previously assessed with LEDs in a rodent model.Objective: We examined LED-induced retinal neuronal cell damage in the Sprague-Dawley rat using functional, histological, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 17 publications
10
96
0
2
Order By: Relevance
“…Using a comparable set of experiments Shang's team recently show that white LEDs lead to photoreceptors death [58], with an important oxidative stress, as we confirmed in this paper, however, according to our data, apoptosis is not the major pathway involved in photoreceptor demise. Actually, the experimental design of Shang's et al has several differences with ours but two differences are very important: first they use dark adapted animals, a procedure that increases retinal sensitivity to light.…”
Section: Discussionsupporting
confidence: 79%
“…Using a comparable set of experiments Shang's team recently show that white LEDs lead to photoreceptors death [58], with an important oxidative stress, as we confirmed in this paper, however, according to our data, apoptosis is not the major pathway involved in photoreceptor demise. Actually, the experimental design of Shang's et al has several differences with ours but two differences are very important: first they use dark adapted animals, a procedure that increases retinal sensitivity to light.…”
Section: Discussionsupporting
confidence: 79%
“…They showed that decrease of visual function, accompanied with ONL atrophy, and increased markers of oxidative stress in response to blue LED light exposure for day 9. 21) In mice, blue LED light exposure (1000 lx, 12 h/d, 1 week) induced phospholipid oxidation and upregulated monocyte chemoattactant protein-1, whereas blue LED light exposure (500 lx, 12 h every 2 d, for 4 or 6 month) induced angiogenesis in another study. 22) These models are not adequate to assess drug efficacy as the timelines are long, whereas the model presented in this study, which demonstrated retinal injury 5 d after exposure may be appropriate for investigating the mechanism of retinal damage as well as the potential interventions to reverse or alleviate damage induced by blue LED light.…”
Section: Discussionmentioning
confidence: 94%
“…Previous blue LED-induced retinal damage model caused the damage by directly exposure of blue LED to eye under ketamine-xylazine anesthesia or exposure in cage that mice were moving freely. [19][20][21][22] Previous report showed that the light-induced retinal damage was decreased under ketamine-xylazine anesthesia. 23) We used the mirrored device separated individually by clear board for the reflection of blue LED light in non-anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no evidence this is the case for humans, animal experiments with LED light discovered greatly hastened macular degeneration (Sliney 1984;Shang et al 2014). Additionally, blue-rich displays are also known to influence the circadian rhythms of their users by suppressing the hormone melatonin levels which aids sleep (Cajochen et al 2011).…”
Section: H Health Effectsmentioning
confidence: 99%